2012
DOI: 10.4269/ajtmh.2012.11-0356
|View full text |Cite
|
Sign up to set email alerts
|

Community Sleeping Pattern and Anopheline Biting in Southeastern Iran: A Country Earmarked for Malaria Elimination

Abstract: An important variable in determining the vectorial capacity of malaria mosquito species is the degree of mosquito-human contact. This parameter can be affected by community sleeping behavior and the host-feeding habits of vectors. A cross-sectional study of 775 randomly selected inhabitants, including 385 Baluchi residents and 390 Afghani refugees, was conducted in a malarious area in Sabaz District, Sistan-Baluchestan Province, southeastern Iran. In addition, monitoring of human landing periodicity of main ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…These data also corroborate with the previous observation that the natural active biting behavior of An. culicifacies mosquito occurs in the mid-night (Singh et al, 1995 ; Basseri et al, 2012 ). Surprisingly, sensory appendage proteins (Ac-SAP1 & Ac-SAP2) showed unequivocally an enriched (16-fold for SAP1, p ≤ 0.001 and 6-fold SAP2, p ≤ 0.0001) expression than other tested OBPs.…”
Section: Resultsmentioning
confidence: 99%
“…These data also corroborate with the previous observation that the natural active biting behavior of An. culicifacies mosquito occurs in the mid-night (Singh et al, 1995 ; Basseri et al, 2012 ). Surprisingly, sensory appendage proteins (Ac-SAP1 & Ac-SAP2) showed unequivocally an enriched (16-fold for SAP1, p ≤ 0.001 and 6-fold SAP2, p ≤ 0.0001) expression than other tested OBPs.…”
Section: Resultsmentioning
confidence: 99%
“…This study also showed the negative results of the public awareness of malaria, and it needed to improve continuously. Although more than two-third of the respondents knew at least one main symptoms of malaria: fever and chill were widely termed as common symptoms of malaria, however, the public awareness was still lower than that in other Asia–Pacific counties [ 39 , 40 ] and Iran [ 41 ]. Moreover, only one-third of them know that the mosquito is the vector of malaria transmission and the proportion tend to be much less than that in Myanmar [ 39 ], Iran [ 41 ], Cambodia [ 42 ] and Peninsular Malaysia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…dirus , the most important vector in the greater Mekong region where containment of growing parasite resistance to artemisinin-based drugs will most probably require elimination of transmission at sub-regional level [74].
Figure 9 Estimates of the proportion of human exposure to Asian malaria vector populations that occurs indoors for both unprotected residents ( π h,i ) and users of long-lasting insecticidal nets ( π h,i,n ), from the Solomon Islands [75] , Laos [76] , Iran [17] and Myanmar [77, 78] , calculated as previously described [71, 72] , except that in the Iranian examples, indoor and outdoor biting densities were assumed to be equal because they were not reported separately [17] . Original data from the Solomon Islands and Myanmar were kindly provided by Hugo Bugoro, Tanya Russell, Frank Smithuis and Nick White.
…”
Section: Introductionmentioning
confidence: 99%